Characterization of key upstream asexual developmental regulators in Monascus ruber M7. (December 2022) - Jia, Lili; Huang, Yuyun; Yu, Jae-Hyuk; Stadler, Marc; Shao, Yanchun; Chen, Wanping; Chen, Fusheng
Abstract: Monascus species are traditional edible and medicinal filamentous fungi with a very long history in East Asia, but their sparse production of asexual spores (conidia) limits their large-scale industrial application. Previous studies have revealed that the flbA ortholog plays a negative role in the conidiation of Monascus ruber M7. FlbA, together with FlbB, FlbC, FlbD, FlbE, and FluG, were shown to be upstream development activators (UDAs) in the asexual development pathway in the model fungus Aspergillus nidulans . In the present study, homologs of these UDAs in M. ruber M7 were identified and functionally characterized. Disruption of MrflbB, MrflbD, and MrflbE delayed and decreased conidiation in M7, whereas the deletion of MrflbC or MrfluG resulted in no detectable change in sporulation. Deletion of MrflbA not only increased conidial number but also postponed sexual development in M7. Furthermore, the deletion of some UDAs also affected the production of secondary metabolites, particularly citrinin, whose yields were dramatically decreased in the Δ MrflbC and Δ MrflbA mutants. These findings provide new insights and opportunities to further explore the asexual development mechanism and modify the conidial production in Monascus spp. Highlights: Upstream development activators have been characterized in Monascus ruber M7. The deletion of MrflbC impeded citrinin production. MrflbB, MrflbD, and MrflbE had conserved conidial roles in M7 as found in Aspergillus nidulans . MrflbA balanced sexual and asexual development in M. ruber M7. The deletion of MrfluG showed no effect on conidiation in M. ruber M7.